Neurological impairment of children with history of prematurity and neonatal hyperbilirubinemia - Ida Bagus Subanada; I Komang Kari; Abdul Hamid (Paediatrica Indonesiana, 2003)
Background In premature infants, the incidence of hyperbiliru-binemia is still high. Bilirubin encephalopathy can develop withoutmarked hyperbilirubinemia.Objective To know the incidence of neurological impairment inpremature with hyperbilirubinemia and the association betweenneurological impairment and serum unconjugated billirubin con-centration.Methods A retrospective study was conducted on 54 prematureswith history of hyperbilirubinemia and 54 without history of hyper-bilirubinemia born between 1997 and 1998 and discharged fromSanglah Hospital. Consecutive sampling was done. After univariateanalysis, multivariate analysis was used to identify the associationbetween serum unconjugated bilirubin concentration and neuro-logical impairment at the adjusted age of 318 months.Results There were statistically significant differences in mean ofage and neurological impairment between subjects with and with-out hyperbilirubinemia (p<0.0001 and 0.026). In subjects with hy-perbilirubinemia, univariate analysis showed significant differencesin means of serum unconjugated bilirubin concentration, gesta-tional age, birth weight, and serum albumin concentration betweensubject who had neurological impairment and who had no neuro-logical impairment with p = 0.005; 0.001; 0.002; <0.0001, respec-tively. Multivariate analysis found there were association betweenneurological impairment and serum unconjugated bilirubin concen-tration, gestational age, and serum albumin concentration withp<0.0001; 0.004; and <0.0001, respectively.Conclusion Neurological impairment in subject with hyperbiliru-binemia was greater than subject without hyperbilirubinemia. Se-rum unconjugated bilirubin concentration is one of three factorsthat associated with neurological impairment